The Role of Employment Opportunities in Mediating the Impact of Human Capital and Wages on Provincial Poverty in Indonesia - Mulyadi, Aka; Majid, M. Shabri Abd.; Suriani, Suriani (International Journal of Business, Economics & Financial Studies, 2024)
This study aims to examine the role of employment opportunities in mediating the effects of human capital and wages on poverty across provinces in Indonesia. This study uses secondary annual data from 34 provinces spanning 2015 to 2022 (panel data). The study employs panel data regression analysis for model estimation, with path analysis and the Sobel test used to assess the mediating role. The findings indicate that human capital has a significant negative direct and indirect impact on poverty through employment opportunities. In contrast, wages do not directly affect poverty but have a significant indirect effect through employment opportunities. Employment opportunities negatively influence poverty and act as a partial mediator between human capital and poverty and a complete mediator in the relationship between wages and poverty. Based on these results, it is recommended that policies aimed at enhancing human capital and increasing employment opportunities be implemented concurrently to reduce short- and long-term poverty. Additionally, it is advised that the government prioritize increasing the minimum wage to strengthen the impact of employment opportunities in alleviating poverty over time. Policies that simultaneously target improvements in human capital, employment opportunities, and minimum wages are crucial for significantly reducing poverty across Indonesia's 34 provinces.